A Comparative Analysis of the Injury Patterns and In-Hospital Mortality Rates of Belted and Unbelted Motor-Vehicle Occupants - Puerto Rico, January 2000 to December 2014 - Layrisse, Verónica; García-Rodríguez, Omar; Ramos-Meléndez, Ediel; Rodríguez-Ortiz, Pablo (Puerto Rico Health Sciences Journal, 2018)
Objective: Motor vehicle collisions (MVCs) constitute a leading source of morbidity and mortality worldwide. Seatbelt use has been associated with reduced mortality in MVCs. In Puerto Rico, the impact of seatbelt use on MVC deaths has not been evaluated, although they represent a major public health threat. Therefore, this study aimed to assess the association between seatbelt use and in-hospital mortality at Puerto Rico Trauma Hospital (PRTH). Materials and Methods: A retrospective cohort study of 2,685 MVC patients aged 1 to 96 years was conducted using the Trauma Registry at PRTH, with data collected from 2000 through 2014. The patient data included sociodemographic and clinical variables and outcomes. Logistic regression analyses were used to evaluate the mortality risk of patients of severe MVC-related trauma who had been wearing seatbelts and compare it to the risk sustained by their unbelted counterparts. Results: Seatbelt use was more common in females than it was in males (71% vs. 62%; p<0.001) and more prevalent in older as opposed to younger patients (p<0.001). Belted severe trauma victims suffered less frequently from head injuries than did their unbelted counterparts (p<0.001). The proportions of patients with Glasgow coma scale (GCS) scores of 8 or lower (17% vs. 6%; p<0.001) and Injury Severity Scores (ISSs) of 25 or higher (24% vs. 15%; p<0.001) were greater for the unbelted group. Belted severe trauma victims had a 30% lower in-hospital mortality risk compared to their unbelted peers (ORunadj = 0.70; 95% CI: 0.52–0.92). After adjusting for confounders, this difference in risk was eliminated (ORadj = 1.04; 95% CI: 0.72–1.52). Conclusion: Our findings demonstrate that seatbelt use is associated with fewer head injuries, lower ISSs, and higher GCS scores. This suggests that using seatbelts mitigates trauma severity, thereby reducing the likelihood of in-hospital mortality for those MVC victims who were wearing seatbelts at the time of their accident.